Bitter vetch (Vicia ervilia) seed protein concentrate as possible source for production of bilayered films and biodegradable containers. (October 2016) - Arabestani, Akram; Kadivar, Mahdi; Amoresano, Angela; Illiano, Anna; Di Pierro, Prospero; Porta, Raffaele
Abstract: The manufacture of biodegradable and renewable containers from bitter vetch seed protein-based "bioplastics" was investigated. A bitter vetch seed protein concentrate was prepared and analyzed for proteins, carbohydrates, phenols, other several organic compounds and multi-elements. Protein film forming solutions were cast in the presence of two different glycerol concentrations and the film containing higher plasticizer amount was laminated with an additional corn zein layer. Both lamination process and lower glycerol concentration led to reduce film moisture content, total soluble matter and elongation at break, while both film tensile strength and water vapour barrier properties resulted enhanced. The obtained bioplastics were then processed by a new laboratory plastic moulding equipment specifically designed and fabricated to convert protein-based films to shaped containers. The use of either lower plasticizer concentration or corn zein lamination gave rise to potentially satisfactory vacuum thermoformed containers with acceptable resistance and stability. Graphical abstract: Highlights: Seed bitter vetch protein concentrate (BVPC) was prepared. BVPC was analyzed for proteins, carbohydrates, phenols and other organic compounds. BVPC films were prepared in the presence of glycerol and laminated by corn zein. A moulding equipment converting protein films to containers was designed and fabricated. Vacuum thermoformed containers with acceptable resistance and stability were obtained.